PENERAPAN MEREK TERDAFTAR TIDAK DIGUNAKAN (NON-USE MARKS) ANALISIS KASUS ANTARA INTER IKEA SYSTEM BV DAN PT RATANIA KHATULISTIWA PUTUSAN MAHKAMAH AGUNG NO. 264 K/Pdt.Sus-HKI/2015 - Selvy Handoyo; Suyud Margono (Jurnal Hukum Adigama, 2018)
The development of business competition in the world of trade, making protection of intellectual property rights very important. Especially in the field of brands. Brand is an important thing to use to differentiate between one another by having a certain characteristic. In this paper we will discuss the case of the "IKEA" brand elimination dispute between Inter Ikea System BV and PT Ratania Khatulistiwa, where the lawsuit was filed because of the Inter Ikea System BV that have the "IKEA" brand which has not been used for 3 consecutive years. The case will be analyzed by Law Number 15 of 2001 concerning the provisions regarding the elimination of the mark and regarding the good faith of the trademark registration of application. By examining the case we can find out the proper legal application and dispute resolution in accordance with the case so that it can provide justice for the parties. In accordance with the five precepts of Pancasila, namely "Justice for all Indonesian people".